2013
DOI: 10.1586/1744666x.2013.850030
|View full text |Cite
|
Sign up to set email alerts
|

Agammaglobulinemia: causative mutations and their implications for novel therapies

Abstract: Agammaglobulinemias are primary (inherited) immunodeficiencies characterized by the lack of functional B-cells and antibodies, and are caused by mutations in genes encoding components of the pre-B-cell or B-cell receptor, or their signaling pathways. The known genetic defects do not account for all agammaglobulinemic patients, suggesting that novel mutations underlying the disease remain to be found. While efficient, the current life-maintaining therapy with immunoglobulins and antibiotics is non-curative, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 102 publications
(114 reference statements)
0
24
0
Order By: Relevance
“…A trend towards decrease in CD16 + SLAN + monocytes, which produce high levels of TNF‐α (Wong et al , ), was observed at day 29. To elucidate whether this was directly depending on BTK‐inhibition in monocytes, we measured SLAN expression on monocytes from a patient with XLA, a condition characterized by loss of functional BTK (Vetrie et al , ; Berglof et al , ). Indeed, we observed extremely few SLAN + monocytes (Figure S6), suggesting that their presence depends on BTK signalling and that the observed decrease in CD16 + SLAN + monocytes was related to ibrutinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A trend towards decrease in CD16 + SLAN + monocytes, which produce high levels of TNF‐α (Wong et al , ), was observed at day 29. To elucidate whether this was directly depending on BTK‐inhibition in monocytes, we measured SLAN expression on monocytes from a patient with XLA, a condition characterized by loss of functional BTK (Vetrie et al , ; Berglof et al , ). Indeed, we observed extremely few SLAN + monocytes (Figure S6), suggesting that their presence depends on BTK signalling and that the observed decrease in CD16 + SLAN + monocytes was related to ibrutinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The primary B lymphocytes responding to the vaccine would subsequently maturate into BTK-independent long-lived plasma cells exerting long-term protection. Due to the fact that the B cell receptor is not expressed in plasma cells, this strategy is valid for all primary immunodeficiencies caused by splice site mutations affecting this receptor complex (1).…”
Section: Discussionmentioning
confidence: 99%
“…X-linked agammaglobulinemia (XLA) is the most common form of inherited agammaglobulinemia, accounting for 85% of all cases (1,2). In this disease, a B cell lineage developmental block, manifested at the transition between the pro-B and pre-B cell stages (3), leads to the essential lack of mature B and plasma cells, with a concomitant pronounced reduction of immunoglobulin levels.…”
Section: Introductionmentioning
confidence: 99%
“…BTK is a non-receptor tyrosine kinase that belongs to the TEC family kinases (TFK), which is the second largest family of non-receptor kinases in humans [3]. BTK is known to be an essential component of B cell receptor (BCR) signalling and is involved in B cell differentiation, proliferation and survival [4,5]. Many studies have reported an essential role of BCR signalling in the pathogenesis of several B cell malignancies [6].…”
Section: Introductionmentioning
confidence: 99%